Upward leader development from tall towers in response to downward stepped leaders - Warner, Tom A. (2010 30th International Conference on Lightning Protection (ICLP), 2010)
We present high-speed video observations (up to 11,000 images per second) of downward propagating negative stepped leaders and associated non-connecting and connecting upward leaders from tall towers in Rapid City, South Dakota, USA. These rare time-resolved optical observations allow for 2-dimensional photogrammetric analysis of relative distances, geometry, speeds and timing between downward and upward leaders. These analyses are beneficial in quantifying natural lightning attachment processes and for comparison with current leader attachment models.